Secure Protocols for Developed Cloud Computing - Lakshmidevi, Thade (International Journal of Computer Sciences and Engineering, 2019)
Cloud Computing is a term used to describe both a platform and type of application. Cloud Computing differs from traditional computing paradigms as it is scalable, can be encapsulated as an abstract entity which provides different level of services to the clients, driven by economies of scale and the services are dynamically configurable. Data stored in third party storage systems like the cloud might not be secure since confidentiality and integrity of data are not guaranteed. Though cloud computing provides cost-effective storage services. Hence, many organizations and users may not be willing to use the cloud services to store their data in the cloud until certain security guarantees are made. In this paper, a solution to the problem of securely storing the client’s data by maintaining the confidentiality and integrity of the data within the cloud is developed. The proposed protocols are developed which ensure that the client’s data is stored only on trusted storage servers, replicated only on trusted storage servers, and guarantee that the data owners and other privileged users of that data access the data securely.